Successful Organizational Business Communication and its Impact on Business Performance: An Intra- and Inter-Organizational Perspective - Valiyeva, Aynura; Thomas, Basil John (Journal of Accounting, Business and Finance Research, 2022)
Intra-firm communication is critical for building synergy amongst the internal business units of a firm, enabling employees from various functional departments and ranks to incorporate their decision-making, understanding of organizational objectives, and common norms and culture to achieve increased organizational effectiveness. This study builds on and assesses a framework of the causes and consequences of effective communication in business interactions between customer and supplier firms, as well as the path for efficient communication within a firm. The proposed study’s structural equation modeling (SEM) analysis based on 352 responses collected from firm representatives in different job positions, ranging from marketing to logistics operations, revealed that in terms of intra-organizational communication, organization characteristics and shared values, top management support and style of leadership, and information technology were all significantly related to communication effectiveness. Furthermore, the frequency and variety of interactions enhanced communication outcomes, thus improving company performance. The results revealed that cultural factors were significantly related to communication effectiveness, as well as shared beliefs and goals. The organizational factors of leadership style, top management support, and information technology were significant determinants of effective communication. Among the contextual factors, interaction frequency and diversity were found to be significant. The study also tested the relationship between supplier and supplier firm performance in the context of communication effectiveness and found that they were closely related when trust and commitment were built between business partners.